2020 APWG Symposium on Electronic Crime Research (eCrime) 2020
DOI: 10.1109/ecrime51433.2020.9493258
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of online repeat victimisation and implications for crime prevention

Abstract: This paper explores the characteristics of repeat victimisation (RV) in relation to fraud and computer misuse (F&CM) crimes recorded in Wales, United Kingdom (UK). The wider study included mixed-methods analysis of a sample of cases (n = 10,001) reported by individuals in Wales, over a period of two years (ending in September 2016). In this paper, key results from the quantitative part of this study concerning RV are presented. This paper contributes to an empirically grounded understanding RV with respect to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…At least two studies have found a tendency for a small number of cybercrime victims to be repeat victims, accounting for a disproportionate number of victimization. One study which analyzed data produced by the Office for National Statistics (ONS), based on the Crime Survey for England and Wales (CSEW), found that repeat cybercrime victims accounted for approximately twice the number of reported cybercrimes than one-time victims (Correia, 2020). Another study found that 45% of cyber-fraud victims were repeat victims (Whitty, 2019).…”
Section: Research On Repeated Victimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…At least two studies have found a tendency for a small number of cybercrime victims to be repeat victims, accounting for a disproportionate number of victimization. One study which analyzed data produced by the Office for National Statistics (ONS), based on the Crime Survey for England and Wales (CSEW), found that repeat cybercrime victims accounted for approximately twice the number of reported cybercrimes than one-time victims (Correia, 2020). Another study found that 45% of cyber-fraud victims were repeat victims (Whitty, 2019).…”
Section: Research On Repeated Victimizationmentioning
confidence: 99%
“…Theories focusing on the influence of culture on phishing susceptibility, account for the broader influence that sociological factors can have on attitudes and behavior (Butavicius et al, 2016;Posey & Canham, 2018); however, because repeat clicking behavior appears to only afflict a small portion of user populations, it seems unlikely that this behavior is being driven by cultural influences. Theories focusing on individual differences have examined the influence of individual level factors on phishing susceptibility such as personality traits, expertise, and other individual differences (Halevi et al, 2015;Lawson et al, 2017;Pattinson et al, 2012;Sackett & Walmsley, 2014;Sudzina & Pavlicek, 2017, 2020Uebelacker & Quiel, 2014;Welk et al, 2015;Zhao & Smillie, 2015). Repeat clicking behavior will most likely involve an explanation drawing from an interaction between individual traits and social influence techniques, or situational factors, or a combination of the three of these factors, and thus hybrid theories (Harrison et al, 2016;Uebelacker & Quiel, 2014;Williams et al, 2017) are the most promising potential explanation of factors driving the repeat clicking phenomenon.…”
Section: Research On Repeated Victimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, researchers have leveraged AF data, to better understand reported trends, as well as their implications for policy and practice [ 2 , 7 10 ]. In particular, this data has an enormous potential for researchers as it provides granular detail on each report and, as the author’s previous work demonstrates, allows for the analysis of small geographies and repeat victimisation [ 8 , 11 ]. However, before conclusions are drawn on substantive matters, it is key to develop a thorough understanding of how data sources were collected, evaluate their quality in relation to wider research aims and prepare them for statistical analysis.…”
Section: Introductionmentioning
confidence: 99%